Cross-sectional associations between metabolic syndrome and performance across cognitive domains: A systematic review. Issue 2 (4th March 2019) - Alcorn, Tara; Hart, Elise; Smith, Ashleigh E.; Feuerriegel, Daniel; Stephan, Blossom C. M.; Siervo, Mario; Keage, Hannah A. D.
ABSTRACT: This review aimed to systematically evaluate associations between the Metabolic Syndrome and domain specific cognitive performance from cross-sectional studies. PsycINFO and Medline were searched on 12 January 2017 with the terms "Metabolic Syndrome" and "cogni*." A total of 973 articles were identified, with 26 meeting inclusion criteria. Individuals with Metabolic Syndrome were consistently reported to have poorer performance on executive function tasks that were not adaptations of the verbal fluency task, including the Stockings of Cambridge test, Color-Word Inference Test and Frontal Assessment Battery; findings from adaptations of the verbal fluency test showed less consistent results. Associations with performance in attention/working memory/information processing, memory, language, and construction/motor performance domains were mixed. All studies reporting on perception showed nonsignificant results. Non-language based executive function tasks appear to be the most sensitive tests of Metabolic Syndrome, and hold promise as a cognitive screen and for the tracking of interventions in this group.